Competencies of Dental Hygienists for Oral Care Service for People with Disability - Jae-Young Lee; Young-Jae Kim; Bo-Hyoung Jin (The Korean Society of Dental Hygiene Science, 2020)
Background: Dental treatment has shifted to the center of the community, and the public policy of the country has expanded to support the vulnerable classes such as the disabled. The dental profession needs education regarding oral health services for persons with disabilities, and it is necessary to derive the competencies for this. Therefore, we conducted this study to derive the normative ability to understand the role of a dental hygienist in the oral health service for persons with disabilities and improvement plans for education.Methods: We conducted a qualitative analysis for deriving competencies by analyzing the data collected through in-depth interviews with experts in order to obtain abilities through practical experience. Based on the competency criterion, relevant competency in the interview response was derived using the priori method, and it was confirmed whether the derived ability matched the ability determined by the respondent.Results: The professional conduct competencies of dental hygienists, devised by the Korean Association of Dental Hygiene, consists of professional behavior, ethical decision-making, self-assessment skills, lifelong learning, and accumulated evidence. Also, core competencies of the American Dental Education Association competencies for dental hygienist classification such as ethics, responsibility for professional actions, and critical thinking skills were used as the criterion. The dental hygienist's abilities needed for oral health care for people with disabilities, especially in the detailed abilities to fulfill these social needs, were clarified.Conclusion: To activate oral health care for people with disabilities, it is necessary for dental hygienists to fulfill their appropriate roles, and for this purpose, competency-based curriculum restructuring is indispensable. A social safety net for improving the oral health of people with disabilities can be secured by improving the required skills-based education system of dental hygienists and strengthening the related infrastructure.